Computer technology and a foreign language lesson: a current trend in methodology as a means of motivation in teaching a foreign language - Vereemchuk, Татьяна (Рroblems of engineering and professional education, 2023)
The use of computers in foreign language lessons is the need of the time. The world of the newest information technologies occupies an increasing place in our lives. The purpose of teaching a foreign language is the communicative activity of students, that is, the practical knowledge of a foreign language.